Iodimetric Determination of 2-Mercaptothiazoline,2,5-Dimercapto-1,3,4-thiadiazole and2- Mercapto-4-methyl-5-thiazoleacetic Acid - Ciesielski, Witold; Zakrzewski, Robert; Zlobinska, Urszula (Asian Journal of Chemistry, 2010)
In this paper a method of iodimetric determination of 2-mercaptothiazoline (1), 2,5-dimercapto-1,3,4-thiadiazole (2) and 2-mercapto-4-methyl-5-thiazoleacetic acid (3) in an alkaline media is presented. In the volumetric titration with potentiometric end-point detection, the determination ranges are: 10–500 μmol, 25–125 μmol and 10–1000 μmol for (1), (2) and (3), respectively. In the coulometric determination with biamperometric endpoint detection, 0.20–10 μmol, 0.10–5 μmol and 0.10–10 μmol amounts of (1), (2) and (3), respectively, were successfully determined. Errors and relative standard deviations for all determinations were below 1 and 0.5%, respectively. For compounds (1) and (2) at higher concentration of sodium hydroxide, potentiometric titration curves were unusually shaped. An addition of iodine resulted in a significant potential drop. The examined systems do not reveal Nernstian behaviour.